Relationship between Outward FDI and Home Country Exports: An Empirical Study of Bangladesh - Ravinder; Poonam; Saini, Vijender Pal (Journal of Developing Economies, 2022)
The present paper investigates the association between outward FDI, exports and growth using data from 1990-2021. The novel estimation procedure of ARDL is used in the study to examine the long and short-run dynamics. Further, the causal relationship between outward FDI, exports and growth is also examined. The results imply that exports, OFDI, and economic growth in Bangladesh have a long-term cointegrating relationship. Additionally, FDI from abroad helps to increase the nation's exports. The study's conclusions are supported by the negative coefficient of the error-correcting term. The study provides useful insights for the policymakers of the country.